Ответ:
-2783
Объяснение:
(x^2)^7•(x^12)^2:(x^4)^3=-2783
––––––––––––––––––
x=(x^5)^5
1) (х^2)^7= х ^2*7 = х^14
(х^12)^2= х^12*2 = х^24
(х^4)^3= х^4*3 = х^12
2) х^14 * х^24 = х^14+24 = х^ 38
3) х^38 : х^12 = х^38-12 = х^26
4) (х^5)^5 = х^25
5) х^26/х^25 = -2783
Ответ: х1= -2783, х2= 2783
-2783^26/2783^25 = -2 783
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
-2783
Объяснение:
(x^2)^7•(x^12)^2:(x^4)^3=-2783
––––––––––––––––––
x=(x^5)^5
Verified answer
Ответ:
1) (х^2)^7= х ^2*7 = х^14
(х^12)^2= х^12*2 = х^24
(х^4)^3= х^4*3 = х^12
2) х^14 * х^24 = х^14+24 = х^ 38
3) х^38 : х^12 = х^38-12 = х^26
4) (х^5)^5 = х^25
5) х^26/х^25 = -2783
Ответ: х1= -2783, х2= 2783
-2783^26/2783^25 = -2 783